Association of human myxovirus resistance protein A with severity of COVID-19 - Otto Lehtinen; Niklas Broman; Matti Waris; Tytti Vuorinen; Ville Peltola; Eliisa Löyttyniemi; Jarmo Oksi; Thijs Feuth (BMC Infectious Diseases, 2022)
Abstract Background In this retrospective cohort study, we explored the correlation of blood human myxovirus resistance protein A (MxA) level with severity of disease in hospitalized COVID-19 patients. Methods All 304 patients admitted for COVID-19 in our hospital until 30th of April 2021 were included in this study. MxA was measured from peripheral blood samples in 268 cases. Patients were divided into groups based on their level of MxA on admission. We studied baseline characteristics and severity of disease on admission based on clinical parameters and inflammatory biomarker levels in each group. Severity of disease during hospitalization was determined by the applied level of respiratory support, by the usage of corticosteroids and by the duration of hospitalization. Results Higher MxA levels on admission were associated with a shorter duration of symptoms before admission, and with more severe disease. Adjusted Odds Ratios for any respiratory support were 9.92 (95%CI 2.11–46.58; p = 0.004) in patients with MxA between 400 μg/L and 799 μg/L (p = 0.004) and 20.08 (95%CI 4.51–89.44; p < 0.001) in patients with MxA ≥ 800 μg/L in comparison with patients with initial MxA < 400 μg/L. The usage of corticosteroids was significantly higher in the high-MxA group (77%) in comparison with the intermediate-MxA group (62%, p = 0.013) and low-MxA group (47%, p < 0.001). Conclusions Higher initial levels of MxA were associated with more severe COVID-19. MxA may be a helpful additional biomarker to predict the severity of the disease.